Mucormycosis related knowledge among a sample of the general population in Egypt - Salem, Marwa Rashad; Ataya, Eman F.; Mahmoud, Ahmed Taher; Fathy, Mohamed; Tammam, Ahmed; Zein, Marwa M. (Intelektual Pustaka Media Utama, 2023)
In the fight against COVID-19, the mass usage of broad-spectrum antibiotics and steroids may result in the development or worsening of a pre-existing fungal disease. The researchers conducted the current study among a sample of the general population in Egypt to assess their mucormycosis-related knowledge. The current work was an exploratory cross-sectional study performed via an online survey. The investigators conducted a convenience sampling by looking for large-networked groups on Facebook; 473 completed the questionnaire. It included: socio-demographics, 28 knowledge questions addressing definition, risk factors, modes of transmission, symptoms, and prevention of mucormycosis, and sources of knowledge. The median total knowledge percent score was 58 (9-38). The least median percent score was 25 (0-83) for prevention knowledge. The comparison between knowledge percent score and participants' demographics showed no statistically significant difference. However, the participants working in the medical field had a higher median knowledge percent score, with a p-value <0.05. The major sources of information were cited as being the internet and social media. Despite being educated, and most of the enrolled individuals were university graduates, most participants had insufficient mucormycotic knowledge. This emphasizes the importance of conducting mucormycosis awareness campaigns for the public.